Development of a paired passing training model to improve soccer passing skills in planet soccer school Palembang athletes - Rendi Alfani; Andi Herdinawaty Heril; Muh. Jamil Abdillah; Muh. Khafid Ansori; Agung Rahmat; Hasnur (Jorpres (Jurnal Olahraga Prestasi), 2026)
This study aims to: (1) Develop a paired passing training model to improve soccer passing skills in Planet Soccer School Palembang athletes. (2) Determine the level of feasibility of the paired passing training model to improve soccer passing skills in Planet Soccer School Palembang athletes. (3) Determine the level of effectiveness of the paired passing training model to improve soccer passing skills in Planet Soccer School Palembang athletes. This research is a development research using the Borg and Gall research and development model, which involves the stages of model development with ten development steps/phases, including potentials and problems, data collection, product design, product validation, design revisions, small-scale trials, small-scale revisions, large-scale trials, largescale revisions, and the final product. Soccer learning experts and coaching practitioners carried out validation. Trials consisted of small-scale and large-scale trials and effectiveness tests-data collection techniques included questionnaires for assessing skills and teamwork instruments. Data analysis techniques used qualitative descriptive analysis and quantitative data analysis. The results of the pairedpassing training model to improve soccer passing skills in Planet Soccer School Palembang athletes were deemed feasible; small-scale trial results showed a 84% valid rate for passing skills without revision, and large-scale trials showed a 95.2% valid rate for passing skills without revision.